Anesthesia in a patient with Stiff Person Syndrome - Yagan,Ozgur (2016)
Abstract Stiff Person Syndrome (SPS), typified by rigidity in muscles of the torso and extremities and painful episodic spasms, is a rare autoimmune-based neurological disease. Here we present the successful endotracheal intubation and application of TIVA without muscle relaxants on an SPS patient. A 46 years old male patient was operated with ASA-II physical status because of lumber vertebral compression fracture. After induction of anesthesia using lidocaine, propofol and remifentanil tracheal intubation was completed easily without neuromuscular blockage. Anesthesia was maintained with propofol, remifentanil and O2/air mixture. After a problem-free intraoperative period the patient was extubated and seven days later was discharged walking with aid. Though the mechanism is not clear neuromuscular blockers and volatile anesthetics may cause prolonged hypotonia in patients with SPS. We think the TIVA technique, a general anesthetic practice which does not require neuromuscular blockage, is suitable for these patients.